AN FT-IR SPECTROSCOPIC INVESTIGATION OF IONIC SOLVATION OF ALKALINE EARTH CATIONS WITH DIMETWYLSULFOXIDE IN ANHYDROUS ACETONITRILE (Journal of Sciences, Islamic Republic of Iran)
The interaction between DMSO and alkaline earth perchlorates in anhydrous acetonitrile was investigated by FT-IR spectroscopy. A quantitative study was performed to determine the average number of bonded DMSO molecules using v (SO) and v (C-S) vibrations. Changes in coordination numbers were observed both with increasing atomic numbers and the solvent composition. None of the investigated systems shows any interaction with either perchlorate ions or acetonittile molecules. Apparent equilibrium constants were estimated from the average coordination numbers.